MONITORING THE STATE OF PROFITABILITY AND ASSESSING THE RISKS OF FINANCIAL ACTIVITY OF THE ENTITY USING FINANCIAL DIAGNOSIS - HADA IZABELA DIANA (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2019)
Being essential in the conditions of a dynamic economic environment, assailed by numerous changes, profitability is the expression of any entity earnings, and obtaining the profit as a measure of profitability (income increase in relation to the reduction of costs) represents the main objective of the activity of an economic entity. The purpose of this article is evaluation the state of profitability and assessing the risks using the financial diagnosis of profitability, as a measure of monitoring the financial health of the entity. Research shows that the financial diagnosis of profitability gives us a realistic view of the entity's financial health by identifying risks, strengths and weaknesses, vulnerabilities, of any threats that may arise in relation to business efficiency. The diagnosis of the state of profitability represents a measure of prevention of risks that threaten the development of the business entity, which allows the formulation of financial recovery paths of activity, to be used by stakeholders to justification of opinions.